Electron Acceleration by a Chirped Short Intense Laser Pulse in Presence of an External Axial Magnetic Field in Vacuum With Different Phase Values - Singh, Ravindra; Sandeep, .; Kaur, Jaspreet (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
We investigated electron acceleration by a chirped short intense laser pulse in presence of an external magnetic field. The retained electron energy is very high with frequency chirp on increasing the value of chirp parameter and constant value of laser intensity parameter. Also, the retained electron energy increases on increment of laser intensity parameter. A linear frequency chirp \(ω (t ) =ω_0 (1-α t)t\) was considered, here \(ω _0\) is the laser frequency at \(z=0\) and \(α\) is the frequency chirp parameter. On increasing the chirp parameters corresponding to the magnetic field with phase then the retained electron energy become so high. Also, we study the variation of the relativistic factor gamma \((γ)\) and the laser intensity parameter \((a _0 )\); also the variation of the relativistic factor gamma \(( γ )\) and the magnetic field \((b_0)\) with different values of the phase, \(φ=0\), \(π /4\) and \(π/2\), respectively. As the time duration is increased the energy gain increased.